2018
DOI: 10.1103/physrevb.98.075413
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of a quantum dot coupled to magnetic leads by Rashba spin-orbit interaction

Abstract: We consider a single-level quantum dot coupled to two leads which are ferromagnetic in general. Apart from tunneling processes conserving electron spin, we also include processes associated with spin-flip of tunneling electrons, which appear due to Rashba spin-orbit coupling. Charge and heat currents are calculated within the non-equilibrium Green's function technique. When the electrodes are half-metallic (fully spin polarized), the Rashba spin-orbit coupling leads to Fano-like interference effects, which res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The theoretical proposal by Bergenfeldt et al 245 has had significant impact. In particular, the hybrid engine found attention in work on thermoelectrics with quantum dots [260][261][262][263][264][265][266][267][268][269] and other quantum heat engine designs [270][271][272][273][274] .…”
Section: Hybrid Quantum-classical Enginementioning
confidence: 99%
“…The theoretical proposal by Bergenfeldt et al 245 has had significant impact. In particular, the hybrid engine found attention in work on thermoelectrics with quantum dots [260][261][262][263][264][265][266][267][268][269] and other quantum heat engine designs [270][271][272][273][274] .…”
Section: Hybrid Quantum-classical Enginementioning
confidence: 99%
“…The role of spin, including Zeeman spin [20] and spin-orbit coupling such as the Rashba effect [21], in thermal transport has been of interest for investigating thermospin current in non-conventional spintronic devices. It is shown that the Rashba spin-orbit coupling forms Fano-like interference effects, which result in an enhanced thermoelectric response [22]. Tuning the Rashba coefficient, anti-crossings in the energy spectrum have been observed leading to the Aharonov-Casher destructive phase interference in the quantum ring system [23,24].…”
Section: Introductionmentioning
confidence: 99%